CD4+ T-cell gene expression of healthy donors, HIV-1 and elite controllers: Immunological chaos. (July 2016) - Nunnari, G.; Fagone, P.; Condorelli, F.; Nicoletti, F.; Malaguarnera, L.; Di Rosa, M.
Highlights: HIV patients and the EC showed an upregulation of the Th1 pro-inflammatory cytokines and chemokines. HLA class I/II genes resulted significantly upregulated in CD4 T cells of HIV and in Elite Controller. Syncytial molecules upregulation in CD4 T cells of HIV assisting the formation of syncytia with APC cells. Abstract: Objectives: T-cell repertoire dysfunction characterizes human immunodeficiency virus type 1 (HIV-1) infection, but the pathogenic mechanisms remain unclear. Disease progression is probably due to a profound dysregulation of Th1, Th2, Th17 and Treg patterns. The aim of this study was to analyze the features of CD4+ T cells in HIV-positive patients with different viroimmunological profile. Methods: we used a gene expression dataset of CD4+ T cells from healthy donors, HIV+ naive patients and Elite Controllers (EC), obtained from the NCBI Gene Expression Omnibus (GEO, http://www.ncbi.nlm.nih.gov/geo/, accession number GSE18233). Results: Principal Component Analysis (PCA) showed an almost complete overlap between the HIV-infected and EC patients, which cannot easily explain the different responses to HIV infection of these two group of patients. We have found that HIV patients and the EC showed an upregulation of the Th1 pro-inflammatory cytokines and chemokines, compared to the controls. Also, we have surprisingly identified IL28B, which resulted downregulated in HIV and EC compared to healthy controls. We focused attention also on genes involved in the constitution of the immunological synapse and we showed that HLA class I and II genes resulted significantly upregulated in HIV and in EC compared to the control. In addition to it, we have found the upregulation of others syncytial molecules, including LAG3, CTLA4, CD28 and CD3, assisting the formation of syncytia with APC cells. Conclusions: Understanding the mechanisms of HIV-associated immunological chaos is critical to strategically plan focused interventions.